Movement patterns of spotted grunter, Pomadasys commersonnii (Haemulidae), in a highly turbid South African estuary - Childs, Amber-Robyn (Rhodes University, Faculty of Science, Department of Ichthyology and Fisheries Science, 2006)
The principal objective of this thesis was to gain an understanding of the movement patterns of spotted grunter Pomadasys commersonnii, an estuarine-dependent fishery species, in the turbid, freshwater dominated Great Fish Estuary. Both manual and automated telemetry methods were used to monitor the movements of spotted grunter during two separate studies conducted in summer and spring 2003 and 2004. Acoustic transmitters were surgically implanted into twenty spotted grunter with lengths between 263 and 387 mm TL in the first study and twenty spotted grunter ranging between 362 and 698 mm TL in the second study. The specific objectives were to gain an understanding of (i) the time spent in the estuarine environment (ii) the space use and home range size, and (iii) the abiotic factors governing the movement patterns of spotted grunter in the estuary. The nursery function of estuarine environments was highlighted in this study as adolescent spotted grunter spent a significantly larger proportion of their time in the estuary than adult fish (p < 0.0001; R² = 0.62). The increased frequency of sea trips, with the onset of sexual maturity, provided testimony of the end of the estuarinedependent phase of their life-cycle. Although considered to be predominantly marine, the adult spotted grunter in the Great Fish Estuary utilised the estuary for considerable periods. Adults are thought to frequent estuaries to forage, seek shelter and to possibly rid themselves of parasites. During this study, the number of sea trips made by tagged fish ranged from 0 to 53, and the duration ranged from 6 hours to 28 days. The tidal phase and time of day had a significant effect (p < 0.05) on the sea trips undertaken by fish. Most tagged spotted grunter left the estuary during the night (84%) on the outgoing tide, and most returned in the evening (77%) during the incoming tide. Sea temperature (p < 0.0001; R² = 0.34), barometric pressure (p = 0.004; R² = 0.19) and wind (p = 0.01) had a significant effect on the number of spotted grunter recorded in the estuary. Spotted grunter were more prone to return to the estuary after high barometric pressure, when low sea temperatures (upwelling events) prevailed. There was a significant positive relationship between home range size and fish length (p = 0.004; R² = 0.20). Small spotted grunter (< 450 mm TL) appeared to be highly resident, with a small home range (mean size = 129 167 m²), that was generally confined to a single core area. Larger individuals (> 450 mm TL) occupied larger home ranges (mean size = 218 435 m²) with numerous core areas. The home ranges of small and large spotted grunter overlapped considerably yielding evidence of two high use areas, situated 1.2 km and 7 km from the mouth of the Great Fish Estuary. Tagged spotted grunter were located in a wide range of salinity, turbidity and temperature, but were found to avoid temperatures below 16 ºC. The daily change in environmental variables (salinity, temperature and turbidity) had a significant effect on the change in fish position in the estuary (p < 0.0001; R² = 0.38). The distribution of tagged spotted grunter, particularly the larger individuals, in the Great Fish Estuary was influenced by the tidal phase (p < 0.05); they moved upriver on the incoming tide and downriver on the outgoing tide. This study provides an understanding of the movement patterns of spotted grunter in the estuary and between the estuarine and marine environments. Consequently, it provides information that will assist in the design of a management plan to promote sustainability of this important fishery species. The techniques used and developed in this study also have direct application for further studies on other important estuarinedependent fishery species.
Keywords: Grunts (Fishes) -- South Africa -- Great Fish River; Pomadasys -- South Africa -- Great Fish River; Freshwater fishes -- South Africa -- Great Fish River; Fishes -- Behavior -- South Africa -- Great Fish River; Estuarine fishes -- South Africa -- Great Fish River; Estaurine ecology -- South Africa -- Great Fish River; Marine ecology -- South Africa -- Great Fish River